2010
DOI: 10.1021/ci900451v
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Hieroglyphs: Abstract Depiction of Complex Void Space Topology of Nanoporous Materials

Abstract: In general, most porous materials are so complex that structural information cannot be easily observed with 3D visualization tools. To address this problem, we have developed a special abstract 2D representation to depict all important topological features and geometrical parameters. Our approach involves reducing these structures based on symmetry and perceived building blocks to a compressed, graph representation that allows for quick structure analysis, classification, and comparison.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…In 2010, Haranczyk and co-workers developed a special abstract two-dimensional graph, that is, the T-ring graph, to depict important topological and geometrical features of zeolite frameworks . A T-ring graph is composed of nodes and edges.…”
Section: Structure Descriptionmentioning
confidence: 99%
“…In 2010, Haranczyk and co-workers developed a special abstract two-dimensional graph, that is, the T-ring graph, to depict important topological and geometrical features of zeolite frameworks . A T-ring graph is composed of nodes and edges.…”
Section: Structure Descriptionmentioning
confidence: 99%
“…These allow us to believe that the natural tiling approach and the NBU concept will essentially facilitate the crystallochemical analysis of zeolites (including extra-large-pore zeolite-type frameworks) and search for new microporous and mesoporous materials. One application has been recently proposed by Haranczyk and co-workers; they showed that zeolite natural tilings produce an abstract depiction of the complex void space topology.…”
Section: Discussionmentioning
confidence: 99%
“…Work in this area has led to the prediction of crystal structures of inorganic molecules, [92][93][94][95] as well as the development of methods for visualizing and identifying potential porous materials. 96,97 The simplest QSPR approaches are based on linear regression models, but more sophisticated forms which incorporate genetic algorithms, artificial neural networks, and the Gaussian processes technique have been developed in recent years. 12,[98][99][100] Several other techniques in cheminformatics have been used for the identification of leads not related to regression models.…”
Section: Cheminformatics Modellingmentioning
confidence: 99%